Women’s Roles and Gender Equality in Islam: Insights from Fathul Karim Mukhtashar Tafsir - Adzima, Fauzan (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
The concept of gender equality in Islam is frequently misunderstood, either by those who perceive Islam as restricting women’s roles or by those who advocate absolute equality without acknowledging inherent differences. This study examines the active roles of men and women in Islam through a thematic exegesis of QS. An-Nisa (4):32 and QS. At-Taubah (9):71, using Fathul Karim Mukhtashar Tafsir as the primary reference. The findings demonstrate that Islam upholds equality between men and women in matters of faith and the rewards of good deeds, while simultaneously guiding them to fulfill roles consistent with Islamic teachings. Women are granted opportunities to participate in diverse spheres of life, including social engagement and da’wah, provided such activities remain within the framework of religious principles. However, the implementation of this concept faces challenges, particularly due to the pervasive influence of patriarchal culture. Consequently, a comprehensive understanding rooted in authoritative exegesis, supported by appropriate policies, is essential to promote the just and balanced application of Islamic values.